Municipal average building capacity: a strategic instrument for economic and financial sustainability of urban developments - Emília Malcata Rebelo (2014)
The main goal of this research consists in the development of a methodology based on territorial plans and urban morphologies - that supports the computation of how much average gross built surface is allowed in each municipality. It fits into the overall scope of the revision of the juridical regime of Territorial Management Instruments currently taking place in Portugal, in the wake of the approval of the new Portuguese Basis Law of Land Policy, Territorial Ordering and Urbanism. The assessment of building capacity herein proposed supports the application of current territorial management instruments (such as the Municipal Urbanization Tax) or new instruments - based on a fiscal monitoring over urban developments - in a clear, accurate and objective way. It, thus, enables the implementation of the most innovative goals of this new Basis Law: raising equity and social cohesion, and ensuring that urban development processes are sustainable from an economic and financial perspective. The methodology to compute the average municipal building capacity is applied, as a case study, no the municipality of Ourém, considering the classification of spaces and the urban indexes settled in OurémŽs Municipal Master Plan, in FátimaŽs Urban Development Plan, and in the Detail Plans currently enforced. It can be concluded that urban morphologies that derive from territorial plans support the design of new management instruments in order to: (i) strengthen municipal finance, ensuring municipalitiesŽ economic and financial sustainability; (ii) assess, in a clear and objective way, the concrete building capacity of certain urban operations as compared with the municipal average building capacity; (iii) quantify the concrete values that can possibly be collected through current or innovative urban management tools; and (iv) warrant a better equity in the distribution of benefits and charges that accrue from urban development processes.